Maximizing Learning Opportunities in the Teaching of ESL for PUC Students at RGUKT-Basar’s Digital Classrooms: A Comparative Study of Conventional and Digital Classrooms - Neerudu, Vijay Kumar; Prasad, Seepathi (International Journal of Psychosocial Rehabilitation, 2020)
This paper discusses how the ICT enabled classrooms promote language competence with reference to the teaching of English as a second language to the students in the southern Asian countries like India. It is hypothesised that the use of ICT maximises the scope of learning opportunities in acquiring LSRW skills in an ESL context in comparison with the conventional mode of teaching. Moreover the conventional mode of teaching and learning has limitations owing to cultural, geographical, social, economic, and pragmatic usage of language. It is a hard nut to crack for teachers to teach LSRW skills effectively in such circumstances. It calls for the use of appropriate illustrations, use of suitable activities etc. As learning is primarily a complex process, the inventions of 21st century technology in teaching and learning especially in Indian ESL context, throw up several challenges for teachers in maximizing the learning opportunities with the growing demand. The present study attempts to maximise the learning opportunities in acquiring language skills using ICT. The target students are pursuing their Pre University Course (PUC) at RGUKT-Basar, one of the reputed institutes in the state of Telangana in India. The data has been collected from a diagnostic test conducted on role-play topics administered to 70 students. The students have been divided into two groups A) Conventional classroom learners (30) and B) Digital classroom learners (40). The classification was made based on their medium of instruction, and kind of classroom provided. The findings from the study show that digital classroom learners performed better in several speaking activities for both the group of learners based on the module selected from the prescribed syllabus by the Board of Intermediate.